Enhanced Oilfield-Produced-Water Treatment Using Fe3+-Augmented Composite Bioreactor: Performance and Microbial Community Dynamics - Qiushi Zhao; Chunmao Chen; Zhongxi Chen; Hongman Shan; Jiahao Liang (Bioengineering, 2025)
The presence of recalcitrant organic compounds in oilfield-produced-water poses significant challenges for conventional biological treatment technologies. In this study, an Fe3+-augmented composite bioreactor was developed to enhance the multi-pollutant removal performance and to elucidate the associated microbial community dynamics. The Fe3+-augmented system achieved efficient removal of oil (99.18 ± 0.91%), suspended solids (65.81 ± 17.55%), chemical oxygen demand (48.63 ± 15.15%), and polymers (57.72 ± 14.87%). The anaerobic compartment served as the core biotreatment unit, playing a pivotal role in microbial pollutant degradation. High-throughput sequencing indicated that Fe3+ supplementation strengthened syntrophic interactions between iron-reducing bacteria (Trichococcus and Bacillus) and methanogenic archaea (Methanobacterium and Methanomethylovorans), thereby facilitating the biodegradation of long-chain hydrocarbons (e.g., eicosane and nonadecane). Further metabolic function analysis identified long-chain-fatty-acid CoA ligase (EC 6.2.1.3) as a key enzyme mediating the interplay between hydrocarbon degradation and nitrogen cycling. This study elucidated the ecological mechanisms governing Fe3+-mediated multi-pollutant removal in a composite bioreactor and highlighted the potential of this approach for efficient, sustainable, and adaptable management of produced water in the petroleum industry.